Notifications

Latest Jobs Updates Upcoming Exam Updates Admit Card - Call Letter Download Latest Exam and Interview Results Subscribe to Notifications

Logarithms

Formulae :
logb(x ∙ y) = logb(x) + logb(y)
logb(x / y) = logb(x) – logb(y)
logb(x y) = y ∙ logb(x)
logb(c) = 1 / logc(b)
logb(x) = logc(x) / logc(b)
f (x) = logb(x) ⇒ f ‘ (x) = 1 / ( x ln(b) )
∫ logb(x) dx = x ∙ ( logb(x) – 1 / ln(b) ) + C
logb(0) is undefined
logb(1) = 0
logb(b) = 1
lim logb(∞) = ∞, when x→∞

Example-
Simplify: log 2 + 2log 3 – log 6

Explanation:
= log 2 + log 3² – log 6
= log 2 + log 9 – log 6
= log (2 × 9) – log 6
= log 18 – log 6
= log (18/6)
= log 3